Cartilage Regeneration: Encapsulated Mesenchymal Stromal Cell Microbeads Promote Endogenous Regeneration of Osteoarthritic Cartilage Ex Vivo (Adv. Healthcare Mater. 8/2021). Issue 8 (21st April 2021) - Sahu, Neety; Agarwal, Pranay; Grandi, Fiorella; Bruschi, Michela; Goodman, Stuart; Amanatullah, Derek; Bhutani, Nidhi
Abstract : In article number 2002118, Nidhi Bhutani and co‐workers employ microencapsulation of mesenchymal stromal cells (MSCs) in alginate hydrogels to sequester MSCs and study their specific paracrine effects in response to patient‐derived osteoarthritic (OA) cartilage. The secretome of microencapsulated MSCs, primed to OA cartilage, is able to promote endogenous regeneration in OA cartilage ex vivo by orchestrating a proliferative and anti‐apoptotic microenvironment.